PENGARUH KEPUASAN DAN LOYALITAS PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK VIVA COSMETICS DI SURABAYA - Okta Faudika Amiarti (CV. Denasya Smart Publisher, 2025)
This study thoroughly explores the key drivers behind consumer decisions to purchase Viva Cosmetics products in Surabaya, centering on two primary factors: customer satisfaction and loyalty. In this context, satisfaction was assessed based on consumer perceptions of product quality, price fairness, and the service received. Meanwhile, loyalty was evaluated by the desire to repurchase, faithfulness to the Viva brand, and the willingness to recommend it to others. To answer this, the study employed a quantitative approach, distributing questionnaires to 107 Viva consumers in Surabaya. The selected respondents were young adults aged 17-30 with a monthly income ranging from IDR 1 million to IDR 3 million. All collected data was then thoroughly analyzed using multiple linear regression. The findings were unequivocal: customer satisfaction proved to be a powerful driver of purchasing decisions. Furthermore, loyalty played an equally crucial role. When examined collectively, both factors made a substantial contribution to a consumer's decision to buy the product. This result offers a key insight: the path to encouraging repeat purchases lies in continuously strengthening customer loyalty. This can be achieved by consistently enhancing product quality, delivering excellent service, and building a powerful brand image.